REAKSIHARGA SAHAM TERHADAP PENGUMUMAN PERUBAHAN PERINGKAT OBLIGASI (Studi Pada Bursa Efek Indonesia tahun 2008-2012) - , ADITYA KHRISNA MURTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Investors in making investment certainly needs information in their investment decisions . One of the available information in the market is the change in bond ratings . This study aims to determine the stock price reaction due to a change in the bond rating companies listed in Indonesia Stock Exchange . The data used is the rating announcements published by PT Pefindo. This study was conducted in 59 rating change events comprises 40 upgrading ratings and 19 downgrading rating events of bonds in the period 2008 to 2012. This study uses one- sample t - test with a 11-days observation period , which is 5 days before the event ( t - 5 ) , current event ( t0 ) , and 5 days after the event ( t +5 ) . Sampling method using purposive sampling . Results of this study is that a upgrading bond ratings significantly positive effect on stock prices. Likewise significant results occurred in downgrading bond ratings show negative effect. Capital market in Indonesia is quite efficient to accept the information provided by the market .